Project of Russian Consensus on gestational diabetes mellitus: diagnostics, treatment and postnatal care - Ivan Ivanovich Dedov (Endocrinology Research Centre, 2012)
Current document presents a coherent viewpoint of Russian Association of Endocrinologists and Russian Association of Obstetriciansand Gynaecologists on diagnostic criteria of gestational diabetes mellitus (GDM) and other glycemic disorders during gestation. Currentapproach is based on analysis of high-profile multinational study HAPO (Hyperglycemia and Adverse Pregnancy Outcomes Study),which included more than 23 000 pregnant women. This project was repeatedly reviewed on workgroup sessions and presented orallyon 6th Russian Congress of Endocrinology with international participation, as well as Russian interdisciplinary educational congressGestational Complications and Premature Delivery.